'Current trends in lower limb Doppler scanning in Ireland'. Issue 1 (January 2023) - Lunney, A.; Donovan, T.
Abstract: Introduction: The clinical need to diagnose and treat above knee deep vein thrombosis (AKDVT) has long been established in literature and in practice. On the other hand, the need to diagnose and treat below knee deep vein thrombosis (BKDVT) continues to be debated in literature. This has resulted in variation in clinical guidelines and protocols nationwide. This research aims to establish if there is a standard practice in Irish ultrasound departments and if so, what that practice is and where sonographers are getting information to inform this. Methods: A questionnaire was designed using SurveyMonkey and distributed using online platforms. The questionnaire aimed to establish the experience of the sonographer, the types of exams performed, protocols/guidelines used as well as scenarios where the sonographer might deviate from protocol. Results: The study yielded 90 responses. The research found 49% of sites perform whole leg ultrasound routinely and 46% perform proximal ultrasound only. 41% of respondents said their protocols were based on clinical guidelines however, 22% of participants didn't know what these guidelines were. 49% of respondents were unaware of what treatment a patient would receive in cases where there is a high clinical suspicion of DVT, but the ultrasound is negative for DVT. Conclusion: The research has established a lack of consistency amongst sonographers and scanning practices with a fairly even split (49% of respondents perform whole leg ultrasound and 46% perform proximal only). Not only has the research identified a lack of standardised scanning approach nationwide, but inconsistencies are also seen in the guidelines that inform our department's protocols as well as inconspicuous terms used in radiology reporting and jargon in literature in relation to DVT. Implications for practice: 1. An inconsistency in practice has been established. Discussions are now needed to decide what guidelines should be implemented into Irish Ultrasound DVT protocols. 2. A national protocol for BKDVT would result in all patients in Ireland having access to the same standard of care. 3. Call for consensus on appropriate training for sonographers undertaking LLDs.